The Sahara from the Bioclimatic Viewpoint: Definition and Limits - Houeron, H N.Le (Annals of Arid Zone, 2016)
The Sahara occupies an area of almost nine million sq. km in Africa and lies in the zone of less than 100 mm mean annual rainfall. It offers a great bioclimatic diversity. There is a Mediterranean Sahara in the north, a Tropical Sahara in the south, a Central Plains Sahara, a Montane Sahara and an Oceanic Sahara, all of which have their own distinctive climatic pattern and biological diversity. Distribution pattern of plants and animals is closely linked with the climatic parameters, particularly the amount and seasonality of rainfall and temperature. The latter may play as important a role as the former in controlling animal and plant distribution since Mediterranean species may dominate in higher elevations under tropical rainfall regimes, whereas Tropical species may intrude the Mediterranean rainfall regions wherever winter temperature is mild or warm.